Penerapan Nilai-Nilai Piagam Madinah Sebagai Konstitusi Islam Dalam Mencegah Radikalisme di Pesantren Darul Istiqamah Biroro - Hamka; Indra Satriani; Harmilawati; Irmayanti (Fakultas Syariah Institut Ilmu Keislaman Zainul Hasan, 2022)
Abstrac There are several facts that make Islamic boarding schools as a place to develop radical ideas in Indonesia, so the authors conducted research at the Darul Istiqamah Islamic Boarding School Biroro, East Sinjai District. This place once carried out an extreme enforcement of Islamic law in Sinjai Regency, which was spearheaded by the Joint Forum for the Mass Movement (FORBES GAMAS). Forcing the will to be followed to fight for the Islamic law. Where this mass prioritizes punishment for thieves, alcohol drinkers, and gamblers without the legal process that applies in Indonesia. On the other hand, it is very contrary to the values ​​that have been practiced by the Prophet in Medina. The purpose of this study is to find out the application of the values ​​of the Medina Charter at the Darul Istiqamah Islamic Boarding School and to Know the Strategy to Prevent Radicalism at the Darul Istiqamah Islamic Boarding School. This research is a qualitative descriptive study with a sociological approach. The sources of data in this study were obtained from interviews with students, managers and teachers of the Darul Istiqamah Biroro Islamic Boarding School and the surrounding community. Data collection techniques used in collecting research data are interviews, observations and documentation. The Darul Istiqamah Biroro Islamic Boarding School teaches early on the values ​​of the Medina Charter to its students by applying the practice directly in the lives of the surrounding community, namely by helping residents or congregations in need. students are taught to help each other, tolerance, respect for others, mutual cooperation and so on. To uphold equality or brotherhood. Radicalism is trying to be avoided as much as possible by the management of the Darul Istiqamah Biroro Islamic Boarding School by enlightening the messages during religious studies that radical ideas are very much against the teachings of Islam and the constitution in force in the Unitary State of the Republic of Indonesia (NKRI). Keywords: Medina Charter, Islamic Constitution, Radicalism